Dynamic Impact of Inflation and Exchange Rate in Indonesia's Top 10 Market Capitalization Companies: Implications for Stock Prices - Hardi, Irsan; Idroes, Ghalieb Mutig; Utami, Resty Tamara; Dahlia, Putri; Mirza, Muhammad Alfin Falha; Humam, Rais Aulia; Chairunnisa, Rizka; Hardia, Natasha Athira Keisha; Mahdani, Rimal (Indatu Journal of Management and Accounting, 2023)
Macroeconomic factors are widely believed to have a crucial role in affecting a company's financial health and, ultimately, its stock price. The study addresses this important issue by investigating the long-term impact of inflation and exchange rates on firm stock prices. This study adopts both panel and cross-firm modeling, along with a dynamic approach, which no prior study has ever conducted in Indonesia’s top 10 market capitalization companies. It utilizes monthly data spanning from September 2008 to August 2023. To generate insights into long-term effects, the study applies the Dynamic Ordinary Least Squares (DOLS) method, with a robustness check using the Fully-Modified Ordinary Least Squares (FMOLS) method. The econometric estimations yield results that are consistent with the hypotheses, indicating that the rise in inflation levels has a negative effect, while the strengthening of the domestic currency in exchange rates positively influences firm stock prices in the long term. This implies that investors should carefully assess and navigate inflationary environments, consider diversifying their portfolios across industries and international markets, and maintain a long-term perspective when making investment decisions in the unique context of Indonesia's market landscape.